Imagens e memórias na construção da cidade de Belo Horizonte - Antonio Milton Signorini (2017)
The process of building the city of Belo Horizonte occurred within theperspective of building memories, oblivion and erasure. There is, onthe one hand, the substitution of recent historical memory for officialmemory, built through the mechanisms of forgetting and erasing. Onthe other hand, individual and collective memories remain, cultivatedand shared despite the official history, being preserved for guardingthe foundations of the construction of identities and their traditions.The erasure was first promoted by the removal of the entire populationof the existing village, so that the place was inhabited with a new andmultiple population in its origins, possessing plural identities, habits andtraditions, loaded with affections, Speculations and impressions aboutthe new locality and a new regime of government. A population thatmust adhere to a new order about which they know little or nothing, butwhose goal is to align the country with the more civilized nations towardprogress. The adjustment of society, which had not had enough time toassimilate the new social structure that had emerged from the abolition,would not have been easy on favorable terms - under a cohesive regimeof government, clear and with a broad educational project. But this wasnot the case. On the contrary, the process was triggered by an elite thatdid not even have a consensus on the form the Republic would take.